2021
DOI: 10.1007/s11606-021-06731-7
|View full text |Cite
|
Sign up to set email alerts
|

Post-traumatic Stress Disorder Among COVID-19 Survivors at 3-Month Follow-up After Hospital Discharge

Abstract: Background Post-traumatic stress disorder (PTSD) is a severe but treatable mental disorder that develops after a life-threatening traumatic event. Coronavirus disease 19 (COVID-19) hospitalisation is a potentially traumatic experience, especially in severe cases. Furthermore, the unprecedented context of the severe acute respiratory syndrome coronavirus 2 pandemic, with daily media bombardment about COVID-19 mortality, may have amplified life-threatening perception also in patients with moderate i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
108
2
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 125 publications
(122 citation statements)
references
References 35 publications
8
108
2
4
Order By: Relevance
“…Among COVID-19 individuals, those with a severe course of the disease are particularly at risk of developing PTSD (6)(7)(8). Patients who had to undergo medical interventions to maintain or restore vital functions experience particularly intense traumatic stress (13,14).…”
Section: Severe Covid-19 Survivorsmentioning
confidence: 99%
See 3 more Smart Citations
“…Among COVID-19 individuals, those with a severe course of the disease are particularly at risk of developing PTSD (6)(7)(8). Patients who had to undergo medical interventions to maintain or restore vital functions experience particularly intense traumatic stress (13,14).…”
Section: Severe Covid-19 Survivorsmentioning
confidence: 99%
“…The effects of the current as well as of past epidemics on the mental health of survivors can help predict the psychopathological consequences of a severe life-threatening viral disease. Two Italian studies on recovered severe COVID-19 survivors reported that the prevalence of PTSD is 10.4% ( 8 ) and 30.2% ( 7 ), respectively. Additionally, in survivors of the severe acute respiratory syndrome (SARS) during the epidemic that covered 29 countries in 2002/2003, infecting 8,096 individuals, of whom 774 died PTSD was present in 39% of patients 10 months after discharge ( 18 ), and over time the frequency of PTSD even increased, ranging from 42 to 54.5% after 31–51 months from discharge ( 18 20 ).…”
Section: What Groups Have High Risk Of Developing Pandemic-related Ptsd?mentioning
confidence: 99%
See 2 more Smart Citations
“…Constant fighting for breath, the beeping of the instruments, people dying in the nearby beds give them a near-death experience which may cause post-traumatic stress disorder and depression, and other psychiatric disorders after recovery. 5 The fifth impact relates to economic losses, unemployment, food security, and uncertainty about the future. A considerable number of people relying on daily earning lost their livelihood because of quarantine.…”
mentioning
confidence: 99%